Evolution of the insects - Grimaldi, David A. (Cambridge University Press, 2004)
Grimaldi (curator, American Museum of Natural History, NY; he also teaches at Cornell, Columbia, and CUNY) and Engel (ecology, evolutionary biology, U. of Kansas; also curator of the University's Natural History Museum) bring a wealth of knowledge to this impressive volume, which is based on an exhaustive examination of the fossil record. Printed in an oversize (9x12<">) format, and illustrated with copious color plates of fossils and present day specimens, the text details the evolution of insects, with chapters on polyneoptera, paraneopteran orders, holometabola, coleoptera and strepsiptera, hymenoptera, panorpida, and amphiesmenoptera. Chapters are also included that provide an overview of evolution and discuss the process of evolutionary history, the fossilization of insects and methods for their study, and the role of arthropods in the origin of insects. The volume will be of interest to the serious amateur as well as the professional naturalist. An exceptional value.